Preparation, characterization of fish scales biochar and their applications in the removal of anionic indigo carmine dye from aqueous solutions - Achieng, George O (Water science and technology : a journal of the International Association on Water Pollution Research, 2019)
The preparation and applications of Tilapia (Oreochromis niloticus) fish scale biochars (FSB) as an adsorbent in the removal of indigo carmine dye (ICD) from aqueous solutions is described. The biochars were prepared through pyrolysis over a temperature range of 200 °C-800 °C and characterized for surface charge, functional groups, thermal stability, particle size and morphology, elemental composition, crystallinity, and surface area by using pHpzc, Fourier transform infrared (FTIR) spectroscopy, thermo-gravimetric analysis (TGA), transmission electron microscopy/scanning electron microscopy (TEM/SEM), energy dispersive X-ray (EDX) spectroscopy, powder X-ray diffraction (PXRD) and Brunauer-Emmett-Teller (BET) techniques, respectively. Batch experiments were carried out to determine the variation of adsorption process with initial dye concentration, contact time, initial solution pH, adsorbent load, temperature and adsorbent pyrolysis temperature on the removal of the dye. The percentage removal increased with increase in initial dye concentration and adsorbent dosage. A pH of 2 was the most appropriate for the adsorption experiments. The equilibrium data fitted pseudo-first-order kinetics and Freundlich models, while the thermodynamic parameters confirmed that the adsorption process was endothermic